2015
DOI: 10.1371/journal.pone.0140591
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Triticum aestivum Calreticulin gene (TaCRT1) Improves Salinity Tolerance in Tobacco

Abstract: Calreticulin (CRT) is a highly conserved and abundant multifunctional protein that is encoded by a small gene family and is often associated with abiotic/biotic stress responses in plants. However, the roles played by this protein in salt stress responses in wheat (Triticum aestivum) remain obscure. In this study, three TaCRT genes were identified in wheat and named TaCRT1, TaCRT2 and TaCRT3-1 based on their sequence characteristics and their high homology to other known CRT genes. Quantitative real-time PCR e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 99 publications
1
34
0
Order By: Relevance
“…To clarify how TaPUB1 regulates salt tolerance on the transcriptional level, qPCR analysis was performed on several salt stress and antioxidant enzyme‐related genes. These results show that TaPUB1 increased the expression of TaCHP and TaCRT1 , which could upregulate salt tolerance (Figure A, B; Li et al 2010; Xiang et al 2015), while it decreased the expression of TaGBF1 , which decreases stress tolerance (Figure C; Sun et al 2015). We also detected the expression levels of genes encoding ionic transporters; the expression of TdSOS1 , TmHKT1;4 , and TNHX‐1 were increased in TaPUB1 ‐OE (Figure D–F; Brini et al 2009; Amar et al 2013; Feki et al 2014).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…To clarify how TaPUB1 regulates salt tolerance on the transcriptional level, qPCR analysis was performed on several salt stress and antioxidant enzyme‐related genes. These results show that TaPUB1 increased the expression of TaCHP and TaCRT1 , which could upregulate salt tolerance (Figure A, B; Li et al 2010; Xiang et al 2015), while it decreased the expression of TaGBF1 , which decreases stress tolerance (Figure C; Sun et al 2015). We also detected the expression levels of genes encoding ionic transporters; the expression of TdSOS1 , TmHKT1;4 , and TNHX‐1 were increased in TaPUB1 ‐OE (Figure D–F; Brini et al 2009; Amar et al 2013; Feki et al 2014).…”
Section: Resultsmentioning
confidence: 78%
“…Based on the expression levels of marker genes, TaPUB1 could upregulate the expression of TaCHP and TaCRT1 in response to salt stress. TaCHP plays a positive role in stress tolerance by downregulating ABA, and TaCRT improves salinity tolerance in overexpressing plants (Li et al 2010; Xiang et al 2015). However, TaPUB1 could negatively regulate the transcription of TaGBF1, which affects the plant's sensitivity to salt (Sun et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, barley calreticulin 1 ( CRH1 , GenBank: L27348.1) and calreticulin 2 ( CRH2 , GenBank: L27349.1), which are calcium-binding proteins, align to position 141.78 cM and may instead be the genes underlying this QTL (2H, 140–145 cM). Xiang et al 12. have shown that tobacco plants transformed with Triticum aestivum calreticulin gene ( TaCRT1 ) showed higher salinity tolerance compared to their wild-type counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Since the same design has been used to study the two parasite structures, it might also be useful to solve other CRT subgroups, such as plant CRTs, plant parasite CRTs or the testis-specific mammalian CRT2 isoform (Persson et al, 2002). This would help to better define what it is that drives the functional differences of CRTs, an area which is still expanding (Johnson et al, 2001;Qiu et al, 2012;de Bruyn et al, 2015;Xiang et al, 2015) and possibly also to provide structural insights into some CRT2-mutation related diseases (Chiu et al, 2007). Coming back to the two parasite CRTs studied here, if one needs to block them without affecting the host CRT, selective inhibitory peptides or antibodies need to be developed, which is only possible if one can identify distinctive structural features in the parasite CRTs.…”
Section: Discussionmentioning
confidence: 99%